Expert guidelines on the use of Cariprazine in bipolar I disorder: consensus from Southeast Asia - Sulaiman, Ahmad Hatim; Amin, Mustafa M.; Ang, Jin Kiat; Ho, Roger; Nik Jaafar, Nik Ruzyanei; Ng, Chong Guan; Wibowo Nurhidayat, Adhi; Paholpak, Pongsatorn; Pariwatcharakul, Pornjira; Sanguanvichaikul, Thitima; Ung, Eng Khean; Wardani, Natalia Dewi; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Cariprazine, a D3/D2 partial agonist, is one of the few recommended treatment options for bipolar 1 disorder (BP1D) in Southeast Asia. This study aims to generate insights from leading experts on the safe and effective use of cariprazine for BP1D, specifically by formulating practical recommendations not thoroughly covered in the existing literature. Methods: A formal consensus methodology using the modified RAND/UCLA Appropriateness Method was employed to develop consensus recommendations. The methodology included a targeted literature search, creation of clinical scenarios, two rounds of rating of the appropriateness of each scenario on a nine-point Likert scale by an expert panel of psychiatrists from Southeast Asia (n = 13), and a face-to-face discussion among the expert panel between the two rounds of rating. In the absence of disagreement, scenarios were classified as appropriate (7–9), equivocal (4–6), or inappropriate (1–3) based on median scores. Clinical scenarios were subsequently converted to consensus recommendations upon approval by the expert panel. Results: Most experts recommended a 4–8-week trial of cariprazine for bipolar depression (85%) and 3–4 weeks for acute mania/mixed (71%). For longer treatment, 61.5% and 69% recommended >1 year for acute mania/mixed and bipolar depression, respectively. Cariprazine was also considered suitable as first-line therapy, including for first-episode bipolar depression (Mdn: 8, IQR: 7–9) and first-episode mania (Mdn: 8; IQR: 8–9). Conclusions: The consensus recommendations may serve as practical guidance for clinicians to make informed decisions regarding the management of adult patients with BP1D, while considering the preferences and circumstances of individual patients.